Pelatihan Pembuatan Edible Film sebagai Upaya Penguatan Keterampilan Penelitian Kelompok Siswa SMP - Arviani Arviani (Universitas Negeri Gorontalo, 2026)
Edible-film production training was conducted as a community-engagement activity to strengthen the research experience of two students from SMP Negeri 1 Gorontalo through laboratory practice. The activity took place from May to June 2026 at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Gorontalo, using corn starch, gelatin, and glycerol as the main materials. The programme employed small-group training and mentoring, including an introduction to edible-film concepts, material functions, laboratory safety, demonstration, guided practice, observation of film formation, and reflection on the experiment. Evaluation was descriptive and based on observations of students’ participation in scientific-work stages. The activity indicates that edible films can provide a contextual research-learning topic connecting polymer concepts, sustainable-packaging issues, and laboratory skills. The small-group format enabled intensive guidance in measuring, mixing, heating, casting, observing, and communicating results. As the activity involved only two students participating in OPSI and employed pre-test and post-test measurements, the findings should be interpreted within the limited scope of the participants. Nevertheless, this activity provides a foundation for developing a more systematic student research mentoring programme supported by measurable evaluation instruments.